Observing the Influence of Job Demands, Job Resources, and Family Demands on Work Engagement Moderated by Self-Efficacy - Rangkuti, Samsiah; Harsasi, Meirani; Asih, Daru; Patiro, Shine Pintor Siolemba; Yusriani, Sri (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
According to the Job Demand-Resource Theory, job demands, job resources, and personal resources significantly influence employee performance through work engagement (Bakker & Demerouti, 2017). Furthermore, performance is also affected by demands and resources originating from the family context (Brummelhuis & Bakker, 2012). This study aims to examine the impact of job demands, job resources, and family demands on work engagement, with self-efficacy as a moderating variable. The research was conducted at the Central Statistics Agency (BPS) across various districts/cities in North Sumatra Province, using a sample of 309 employees. The sampling technique employed was systematic random sampling, and the data analysis method used was Partial Least Square-Structural Equation Modeling (PLS-SEM). The study's findings show that both job resources and self-efficacy significantly and positively impact work engagement. This suggests that increases in job resources and self-efficacy are associated with enhanced work engagement. Conversely, job demands and family demands did not significantly affect work engagement. Additionally, the findings reveal that self-efficacy does not significantly moderate the relationship between job demands, job resources, family demands, and work engagement.